Blockchain Paradigms in Public Administration: Blockchain Case Study in Romanian Public Administration - Sorin BURLACU; Mihaela Diana OANCEA-NEGESCU; Svetlana Platagea GOMBOS; Gabriel Laurentiu FRANCU; Maria Alexandra SARBU; Raluca Iuliana GEORGESCU (Communications of International Proceedings, 2021)
The objective of our research is to present blockchain technology from the perspective of its usefulness and functionality to identify possible applications in public administration. The study of the literature and the research carried out have allowed us to identify some essential features of the blockchain that give us hope that this technology is useful and can bring benefits to public administration. In Romania we have identified scenarios and project proposals but also limits that prevent the implementation of this technology. The limitations of our research are that although they describe the reference system that determines how we perceive reality; they behave like headphones for a virtual reality. Thus, for Romania we have identified certain characteristics to focus on but to generalize our recommendations it may be necessary to exceed the limits of the vision on the surrounding world.
Keywords: Public administration; blockchain